An unusual cause of progressive chest deformity in a child - Yusoff, Muhammad Khairul Amri; Abdullah, Ahmad Fadzil; Hasan, Taufiq Hidayat; Abd. Aziz, Azian; Ab. Rahman, Norhafiza; Arasappan, Mohanaprakash K R (IIUM Press, 2024)
Inflammatory myofibroblastic tumour (IMT) is a rare tumour with intermediate malignant potential and unclear aetiology. In most cases, the clinical presentation is non-specific. The liver and lung are the most common location for IMT in children, and mediastinum is an uncommon place. Symptoms vary depending on the location of IMT, thus making a definitive diagnosis to be even more difficult. Until the histological investigation can rule out IMT, it should be considered in the differential diagnosis of individuals with localised masses. We report here a case of an 8-year-old boy with rightsided chest pain and deformity before the diagnosis of mediastinal IMT was made through tissue biopsy.